Evaluation of filling ability of Guttaflow Bioseal sealer to the simulated lateral canal by scanning electron microscope - Hero Mohammed Zahid; Niaz Hama Ghareeb (Erbil Dental Journal)
Background and objectives: Lateral canals establish a connection between the main root canal and periodontal ligament. Any necrotic tissue and bacteria residing in the lateral canals influence the efficiency of the filling of the root canal and the outcome of root canal therapy. The aim of this study was to determine which type of root canal sealer among GuttaFlow Bioseal, AH-Plus and Endosequence BC sealer provides deeper penetration into artificially prepared lateral canals.